Description of a new Myzocallis (Hemiptera Aphididae) living on Valonia oak in Southern Italy with DNA barcoding accounts on allied species-group - Barbagallo, Sebastiano; Cocuzza, Giuseppe E. Massimino (Zootaxa, 2022)
The aphid Myzocallis macrolepidis sp. n. is described from the Apulia region, Italy, where it was collected on Quercus macrolepis. The new taxon has a pale-yellow colour in life as alate viviparous females and paler nymphs. Its life cycle remains unknown at present, as sexual morphs were not yet collected; nevertheless, being the aphid host plant a deciduous oak species, very probably the insect performs a monoecious holocycle. Morphologically most similar aphids are M. occidentalis and M. schreiberi from which the new species can be mainly distinguished by the different ratio of last rostral joint to second hind tarsomer and a few other morphological and ecological features. The molecular analysis also confirms the genetic difference of the new taxon from the other allied congeneric species, and molecular differences are briefly discussed.